to find an equation with specific roots, we have an equation if the form y=A(x-h)(x-k) where the roots are h and k. this is because when you plug in x=h or x=k, you get y=A(h-h)(h-k)=A(0)(h-k) = 0
so for the first question, we have
y=A(x-(-10))(x-(-6))=A(x+10)(x+6)
but the vertex must be at (-8,-8), which means when x=-8, then y=-8
plugging this in we get:
-8=A(-8+10)(-8+6)
-8=A(2)(-2)
-8=A(-4)
A=2
so our final answer is
y=2(x+10)(x+6)
using the same method the answer so the second one is:
y=-(x-2)(x-4)